Genetic diversity, introgression and relationships among West/Central African cattle breeds - (:unkn) unknown (My University, 2004)
Genetic diversity, introgression and relationships were studied in 521 individuals from 9 African Bos indicus and 3 Bos taurus cattle breeds in Cameroon and Nigeria using genotype information on 28 markers (16 microsatellite, 7 milk protein and 5 blood protein markers). The genotypes of 13 of the 16 microsatellite markers studied on three European (German Angus, German Simmental and German Yellow) and two Indian (Nelore and Ongole) breeds were used to assess the relationships between them and the African breeds. Diversity levels at microsatellite loci were higher in the zebu than in the taurine breeds and were generally similar for protein loci in the breeds in each group. Microsatellite allelic distribution displayed groups of alleles specific to the Indian zebu, African taurine and European taurine. The level of the Indian zebu genetic admixture proportions in the African zebus was higher than the African taurine and European taurine admixture proportions, and ranged from 58.1% to 74.0%. The African taurine breed, Muturu was free of Indian zebu genes while its counter Namchi was highly introgressed (30.2%). Phylogenic reconstruction and principal component analysis indicate close relationships among the zebu breeds in Cameroon and Nigeria and a large genetic divergence between the main cattle groups - African taurine, European taurine and Indian zebu, and a central position for the African zebus. The study presents the first comprehensive information on the hybrid composition of the individual cattle breeds of Cameroon and Nigeria and the genetic relationships existing among them and other breeds outside of Africa. Strong evidence supporting separate domestication events for the Bos species is also provided.
Keywords: African Research